Day 2 Thu, February 20, 2020 2020
DOI: 10.2118/199294-ms
|View full text |Cite
|
Sign up to set email alerts
|

Unplugging Standalone Sand Control Screens with High-power Shock Waves: An Experimental Study

Abstract: Previous studies showed that different parameters influence the plugging of completion tools. These parameters include (i) rock mineralogy, (ii) reservoir fluids properties, and (iii) type of completion tools. Although different methods have been used for unplugging these tools, there is still debate regarding performance of these methods on damage removal. In this study, we assessed the performance of high-power shockwaves generated from an electro-hydraulic stimulation (EHS) tool on cleaning c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…This variation shows the mineral heterogeneity of the scale samples. This observation is in agreement with previous studies that showed the mineral heterogeneity of depositing minerals [7,37]. In this sample, there are four regions with different components: (1) organic matter, (2) iron sulfide, (3) Mg-based silicates and (4) calcite/aragonite.…”
Section: Sem/eds Analysissupporting
confidence: 93%
See 2 more Smart Citations
“…This variation shows the mineral heterogeneity of the scale samples. This observation is in agreement with previous studies that showed the mineral heterogeneity of depositing minerals [7,37]. In this sample, there are four regions with different components: (1) organic matter, (2) iron sulfide, (3) Mg-based silicates and (4) calcite/aragonite.…”
Section: Sem/eds Analysissupporting
confidence: 93%
“…Furthermore, the type of the scales used in the petroleum industry varies considerably. Habibi et al (2020) [7] categorized the mineral composition of scale deposits removed from completion tools. They showed that the inorganic scale deposits are mainly silicates, carbonates and corrosion products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation